Volcanic Sediment Layer of Mount Samalas 1257 AD Modeling Based on Seismic Data - Suhayat Minardi; Teguh Ardianto; Alfina Taurida Alaydrus; Hiden Hiden (Institut Teknologi Bandung, 2019)
Research to determine model of sediment volcanic layer of Mountain Samalas 1257 AD has been conducted in Lombok Island. Modeling based to surface wave velocity data which collect use MASW (multichannel analysis of surface wave) method. The method has applied at 6 locations in southern part relatively and models were made on southern and southeastern of eruption source. Grouping of volcanic layer was based on IBC 2003 (ICC, 2003), TSC, 1998 (Ministry of Public Works and Settlement Government of Republic of Turkey, 1998) criteria. Result of modeling was verified using outcrop at the measurement of seismic area. Volcanic layer groups that detect are C, D, E type which have velocity less than 400 ms-1 and it’s thickness less than 50 meters. The volcanic layer group consist of sand, kerikil, clay, batuapung, volcanic ash, and alluvium. All of types of volcanic rocks has founded at all seismic measurement locations with different thickness and composition.